Alarming Pattern of Antimicrobial Resistance in Neonatal Sepsis Observed in Neonatal Intensive Care Unit of a Tertiary Care Hospital in Bangladesh (KYAMC Journal, 2021)
Background: Resistance of micro-organisms to multiple broad-spectrum antimicrobial agents is a major problem in treating neonatal sepsis. It is a matter of utmost importance to have knowledge of trends in changing pattern of antimicrobial resistance.Objective: This study was done to observe antimicrobial resistance of gram-positive and gram-negative bacteria isolated from cases of neonatal sepsisMaterial and Methods: This cross sectional descriptive study was conducted in Department of Microbiology in collaboration with Department of Neonatology, Dhaka Medical College Hospital, Dhaka. Antimicrobial resistance of all the isolated bacteria was performed by Modified Kirby-bauer disk diffusion method following standard guideline after isolation and identification of bacteria from blood samples of suspected septicemic neonates by automated blood culture and standard microbiological protocol.Results: All of the isolated Staphylococcus aureus, Coagulase negative Staphylococcus, Group-B Streptococcus and Micrococcus showed 100% resistance to ceftriaxone, cefotaxime and ceftazidime. Among the isolated gram-negative bacteria, all of Enterobacter spp., Pseudomonas aeruginosa and Citrobacter spp. showed 100% resistance to amoxiclav, amikacin, ceftriaxone, cefixime, ceftazidime.Conclusion: Majority of the gram-positive and gram-negative bacteria are developing resistance to multiple antimicrobial agents and surveillance is necessary to tackle this alarming situation.KYAMC Journal.2021;12(01): 03-07